Implementation of PAP and PAN in learning at school - Ghina Shafiyyah; Nur Khalis Majid (al-Afkar, Journal For Islamic Studies, 2025)
This study investigates the use of Norm-Referenced Assessment (NRA) and Criterion-Referenced Assessment (CRA) as assessment techniques to comprehend high school students' abilities. In CRA, the achievement of predefined standardsor criteria serves as the basis for measuring students' success. By comparison, NRA assesses students' abilities based on how well they perform in relation to a peer group. Additionally, the application of CRA and NRA affects the teaching methodologies employed by instructors, empowering them to modify their approaches in accordance with the demands of their students.